AI Education Across the Curriculum: Design and Pilot Study of a Cross-Disciplinary Module Set - Chao, Jie; Ellis, Rebecca; Jiang, Shiyan; Smyslova, Daria; Li, Qiuqing; Nocera, Amato; Byrd, Christy; Wu, Zhen; Rosé, Carolyn P.; Callahan, Stephen; O'Grady-Cunniff, Dianne (Proceedings of the AAAI Conference on Artificial Intelligence, 2026)
Artificial intelligence (AI) education has garnered growingattention from both educational researchers andpractitioners in recent years. Among the various emergingapproaches, integrating AI education across thecurriculum—particularly within core disciplines—offersdistinct advantages. This strategy foregrounds theinherently interdisciplinary nature of AI and enablesstudents to investigate its connections with subjects suchas mathematics and English language arts (ELA).Furthermore, it holds promise for broadening participationby engaging all students, including those historicallyunderrepresented and underserved in the field of AI. Todate, most efforts to integrate AI education have beensituated within individual classrooms, often led by asingle teacher. While such initiatives provide valuableentry points, they overlook the reality that students’learning experiences span multiple classrooms anddisciplines. As students transition between subjects, theyinevitably synthesize ideas—both consciously andunconsciously—from diverse instructional contexts.Recognizing this, we take a whole-school perspective thatconsiders the cumulative and interconnected nature ofstudents’ learning experiences. With this perspective, weexplore a coordinated, cross-disciplinary approach in whichstudents engage with AI through a set of curriculum modulesspanning mathematics, ELA, and social studies. Each moduleis discipline-specific yet designed to contribute to acohesive, cross-disciplinary exploration of AI. Thesemodules are further framed by a self-paced introductoryunit, which establishes foundational concepts, and aculminating application-and-reflection unit, which supportsintegration and transfer of learning. This paper describesthe design of the AI Education Across the Curriculum moduleset and reports preliminary findings from a pilotimplementation conducted in Spring 2025. By examining boththe pedagogical design and initial findings, we aim tocontribute to the growing body of research on scalable,equitable, and interdisciplinary models for AI education.